(untitled) (Journal of Asian Development Studies, 2024)
This study investigates the influence of social media influencers on the purchasing decisions of youth, focusing on emotional and rational aspects such as attractiveness, credibility, and message content. The main objectives are to examine how these aspects influence youth purchasing decisions and to determine the significance of emotional connections and trust in influencer marketing. Utilizing the Elaboration Likelihood Model, the research employs a cross-sectional design with a sample of 556 participantsaged 15-24, collected via an online survey. Data analysis, including Chi-Square tests, revealed that social media influencer marketing significantly affects youth purchasing decisions. Emotional connections and trust in influencers emerged as crucial factors, with influencers’ attractiveness and credibility significantly influencing purchase intentions. These findings underscore the importance of authenticity and trustworthiness in influencer marketing, suggesting that brands should focus on these elementsto engage youth effectively. The study highlights the influential role of social media influencers in shaping consumer behaviorand provides insights for marketers to develop strategies that resonate with young audiences.